Kebijakan Harga Eceran Tertinggi (HET) : Meng-Counter Stabilisasi Distribusi Liquefied Petroleum Gas (LPG) 3 Kilogram Perspektif Bisnis Islam - Jodi Pratama Putra; Zumaroh (UIN AM. Sangadji Ambon, 2025)
This study analyses the economic impact of the implementation of the Highest Retail Price (HET) policy on LPG distributors at the Sumbergede LPG Base, Sekampung, East Lampung. The issue at hand is that while the HET policy aims to ensure fair pricing for consumers (ideally), its implementation in the field faces challenges such as fluctuating operational costs and supply limitations, forcing distributors in remote areas to sell above HET to cover additional expenses (in reality). Based on this issue, the study formulates the problem regarding the effectiveness of the HET policy, as well as the benefits and challenges faced by distributors. This research aims to evaluate the implementation of the HET policy on LPG distribution, particularly in terms of its economic impact and the balance between consumer interests and distributor business sustainability. A qualitative descriptive approach is employed, with data collected through interviews, observations, and documentation. The findings indicate that while the HET policy provides price stability for consumers, distributors face difficulties in maintaining supply and dealing with rising operational costs. Therefore, operational support and strict supervision are needed to ensure the effectiveness of this policy while considering both distributor welfare and consumer interests.